Reduction of arteriovenous access blood flow leads to biventricular unloading in haemodialysis patients - Valerianova, Anna; Malik, Jan; Janeckova, Jana; Kovarova, Lucie; Tuka, Vladimir; Trachta, Pavel; Lachmanova, Jana; Hladinova, Zuzana; Hruskova, Zdenka; Tesar, Vladimir (International journal of cardiology, 2021)
AIMS: Patients on chronic haemodialysis have a wide range of changes in cardiac function and structure, including left ventricular hypertrophy, dilation and diastolic dysfunction or pulmonary hypertension. All these changes were linked to increased mortality in previous studies. High-flow arteriovenous fistulas (AVF) are supposed to be a factor contributing to their development. This study investigated the early effect of surgical AVF blood flow (Qa) reduction on these changes in patients with or without heart failure changes. METHODS AND RESULTS: Forty-two patients in chronic haemodialysis programme with high-flow AVF (Qa over 1500 mL/min), indicated for surgery for ≥1 of the following indications: 1.manifest heart failure; 2.hand ischemia; 3.advanced structural heart changes detected by echocardiography. The patients underwent echocardiography on selection visit, before blood flow reducing surgery and six weeks thereafter. The Qa reduction led to decrease of left ventricular mass (p = 0.02), end-diastolic volume (p = 0.008), end-diastolic diameter (p = 0.003) and left atrial volume (p = 0.0006). Diastolic function improved. Similarly, right ventricular diameter and right atrial volume decreased (p = 0.000001 and 0.00009, respectively) together with the decrease of estimated pulmonary artery systolic pressure. 81% of patients suffered from pulmonary hypertension prior to surgery, only 36% thereafter. CONCLUSION: The surgical restriction of the hyperkinetic circulation leads to several improvements of heart structure and function, which was linked to higher mortality in other studies. The beneficial effect of Qa reduction is present even in patients without symptoms of heart failure. The contribution of AVF must be considered with structural or functional heart changes.
Keywords: arteriovenózní zkrat; Hemodynamics; Heart Failure; Humans; srdeční selhání; hemodynamika; Echocardiography; High flow arteriovenous fistula; High-output heart failure; dialýza ledvin; lidé; Arteriovenous Shunt, Surgical; Haemodialysis; echokardiografie; Renal Dialysis